Strategy development of tofu agroindustry (Case of Pak Lutfi's Tofu) - Putri, Dini Amalia; Dewi, Ilma Satriana (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The tofu agroindustry is a product made from soybeans which is widely cultivated, especially in Pandau Jaya village, Siak Hulu District, Kampar Regency. One of the tofu industries that has been operating for quite a long time in the area is the "Pak Lutfi" Tofu Industry. This industry experiences problems with the number of workers, expensive raw material prices, and products that have not been diversified. The aim of this research is to analyze development strategies in Pak Lutfi's tofu industry, so that solutions can be provided to the problems faced by this business. The research was conducted using a survey method, with the research respondent being Mr. Lutfi as the business owner. The data analysis used is SWOT analysis and SPACE Matrix. The results of research using SWOT analysis obtained ST strategy results. Meanwhile, for analysis using the SPACE matrix, a strategy is obtained in the form of an aggressive strategy.